Ready to rebuild the imminent plan to rebuild the last days temple - Ice, Thomas; Price, Randall (Eugene, OR Harvest House, 1992)
Includes bibliographical references, photographs, diagrams, etc.
Keywords: Temple Mount (Jerusalem) -- international status; Jewish-Arab relations; Bible -- prophecies -- Temple of Jerusalem